THE ROLE OF CSR COMMUNICATION IN STRENGTHENING CORPORATE REPUTATION - Wan Nor Hidayah Wan Afandi; Jamilah Jamal; Mohd Zuwairi Mat Saad, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This conceptual paper discuss about the role of CSR communication in strengthening corporate reputation. A number of earlier studies argue that for CSR to be impactful on the stakeholders, corporations must communicate CSR information to their stakeholders. Thus, CSR communication plays a role in influencing customers’ perceptions and evaluations of corporate reputation. The author reviewed existing literatures that focus on corporate reputation and CSR communication. The review includes highlights on common measurements of corporate reputation and CSR communication tools and channels. Nevertheless, future studies may want to further investigate the relationship between CSR communication and corporate reputation with other possible mediating or moderating factor such as trust, csr knowledge and csr awareness.